Shoulder arthroplasty - Bigliani, Louis U; Flatow, Evan L (Springer, 2005)
This practical book presents the orthopedic surgeon and resident with a logical, step-by-step guide to successfully performing shoulder arthroplasty. An introductory chapter on surgical approaches and preoperative evaluation serves as a springboard for in-depth examinations of cutting-edge techniques. Topics include total shoulder replacement, glenoid component preparation and soft tissue releases, and revision shoulder arthroplasty. The comprehensive text also addresses conditions such as arthroplasty and rotator cuff deficiency and glenohumeral inflammatory arthritis. Rehabilitation of shoulder arthroplasty is covered as well. To clarify key concepts, the book is generously illustrated with more than 150 images. Specific examples of complications and how to avoid and correct them are also found throughout.
Keywords: Arthroplasty; ortopedie; artroplastika; ramenní kloub; Shoulder; Shoulder Joint; rameno